2019
DOI: 10.1186/s40168-019-0726-2
|View full text |Cite
|
Sign up to set email alerts
|

The occurrence of Listeria monocytogenes is associated with built environment microbiota in three tree fruit processing facilities

Abstract: Background Multistate foodborne disease outbreaks and recalls of apples and apple products contaminated with Listeria monocytogenes demonstrate the need for improved pathogen control in the apple supply chain. Apple processing facilities have been identified in the past as potential sources of persisting L . monocytogenes contamination. In this study, we sought to understand the composition of microbiota in built appl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
63
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
9
1

Relationship

3
7

Authors

Journals

citations
Cited by 59 publications
(68 citation statements)
references
References 74 publications
(66 reference statements)
0
63
0
1
Order By: Relevance
“…The composition of the postharvest microbiome of apple can also be impacted by bacterial and fungal communities present in packing houses that process fruit for market and storage after harvest. A recent study reported substantial differences in both the composition and diversity of the environmental microbiota present in different tree fruit processing facilities, and revealed that the presence of Pseudomonadaceae and Diplodascaceae families was associated with an increased occurrence and persistence of the foodborne pathogen Listeria monocytogenes [15]. Further research on this topic may lead to a better understanding of the interactions that occur between pathogenic and nonpathogenic microorganisms found on harvested fruits and the optimization of fruit handling strategies.…”
Section: Introductionmentioning
confidence: 99%
“…The composition of the postharvest microbiome of apple can also be impacted by bacterial and fungal communities present in packing houses that process fruit for market and storage after harvest. A recent study reported substantial differences in both the composition and diversity of the environmental microbiota present in different tree fruit processing facilities, and revealed that the presence of Pseudomonadaceae and Diplodascaceae families was associated with an increased occurrence and persistence of the foodborne pathogen Listeria monocytogenes [15]. Further research on this topic may lead to a better understanding of the interactions that occur between pathogenic and nonpathogenic microorganisms found on harvested fruits and the optimization of fruit handling strategies.…”
Section: Introductionmentioning
confidence: 99%
“…Microbiome analyses of meat and seafood products provided a microbiological dissection of food spoilage to study microbial origin and population dynamics of the complex process (2). Besides targeted investigations of pathogenic and spoilage microorganisms, overall food microbiome profiles have been investigated to suggest how agricultural and food processing practices affect resident food microbial communities in the context of food safety and spoilage (3)(4)(5). In addition to taxonomic compositions, particular microbiome constituents such as antimicrobial resistance genes (ARGs), or resistomes, have been profiled to indicate the ecological impact of antimicrobial usage at various stages of beef (6) and poultry (7,8) production.…”
mentioning
confidence: 99%
“…This can correspond to either mixed biofilm enhancement or inhibition (Carpentier and Chassaing, 2004;Fox et al, 2014). Nevertheless, a recent study by Tan et al (2019) proved that the composition and diversity of microbiota from food processing surfaces indicates the persistence of the Listeria monocytogenes. This reiterates the need for further investigation on microbiota characterization particularly, on the role of the harmless bacteria in the food safety.…”
Section: Resultsmentioning
confidence: 99%